A longitudinal survey of the gut virome of commercial broiler chickens from prehatch to slaughter. Issue Volume 1(2019)Issue A (8th March 2019) - Trudgett, James; Brennan, David; Casement, Veronica; McAdam, Paul; Smyth, Victoria
Abstract : Uneven flock growth (UFG) occurs when a broiler flock exhibits a wide range of bodyweights at slaughter. Automated chicken processing plants operate on an average bodyweight for the flock being processed so UFG can cause disruption to the processing flow that requires manual remediation. It is known that enteric virus infections of young broiler flocks lead to varying degrees of growth restriction that range from runts at hatch and severe early stunting, which are generally culled, to poor flock performance and UFG. In order to investigate the make-up of communities of enteric viruses (virome) associated with poor growth and also their infection timings and persistence in broiler flocks, a longitudinal survey of 7 commercial broiler flocks of varying performance over 3 successive broiler crops was undertaken with gut and faecal samples collected from 50 birds at each of 12 timepoints from pre-hatch to slaughter. The samples were pooled for each timepoint, then processed to enrich for viruses by removing host cells and bacteria. The RNA was extracted from each timepoint sample, amplified by whole transcriptome amplification followed by whole genome library preparation for the Illumina MiSeq platform and libraries multiplexed. Bioinformatics analysis used ViromeScan which facilitates metagenomic studies of quality-trimmed sequencing reads. The presence of diverse viral families was seen including the known major enteric viruses of the astrovirus, picornavirus, reovirus and parvovirus families. A greater diversity of viruses was observed in the flocks of poorer performance than in those flocks of good performance.